The Investigation of Protein Profile of Different Botanic Origin Honey and Density Saccharose-Adulterated Honey by SDS-PAGE Method - Nisbet, C.; Gürler, Ali Tümay; Çiftçi, G.; Yarim, G.F. (Kafkas University, 2009)
Protein content and quality of honeys are varied according to the plant source as well as production and handling conditions. Lots of methods were developed to determine the botanical origins and qualities of honeys. The aim of this study was to comparatively evaluate the protein profiles of the honeys produced from bee colonies exposed to different plant sources (rhododendron, chestnut, blossom, pine) and feeding (Saccharose nutrition) conditions by using SDS-PAGE method. In this study, the protein profiles, but not protein densities, were found similar between pure honeys produced from rhododendron, chestnut, blossom, pine and high sugared (saccharose) honeys. Three main protein bands (94 kDa, 87 kDa and 84 kDa) were determined in the electrophoretic analysis of the honeys. Protein ratios (%) were determined as 1.31±0.07, 1.02±0.04, 0.90±0.03, 1.16±0.09 and 0.23±0.01, respectively. Protein band densities were found higher in rhododendron, chestnut and pine honeys than those in honeys produced by using excessive saccharose syrup. It was concluded that protein profile can be used in differentiation between pure and adulterated honeys.
Farklı Bitki Türlerinden Üretilmiş Saf ve Şekerli Balların Protein Profilinin SDS-PAGE Yöntemi ile İncelenmesi
Keywords: Honey; Protein Electrophoresis; Saccharose Syrup Honey